2017
DOI: 10.1530/rep-17-0173
|View full text |Cite
|
Sign up to set email alerts
|

Trivial role for NSMCE2 during in vitro proliferation and differentiation of male germline stem cells

Abstract: Spermatogenesis, starting with spermatogonial differentiation, is characterized by ongoing and dramatic alterations in composition and function of chromatin. Failure to maintain proper chromatin dynamics during spermatogenesis may lead to mutations, chromosomal aberrations or aneuploidies. When transmitted to the offspring, these can cause infertility or congenital malformations. The structural maintenance of chromosomes (SMC) 5/6 protein complex has recently been described to function in chromatin modeling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 75 publications
2
19
0
Order By: Relevance
“…Further unpublished data cited by Ralph et al (2016) showed that stress-like levels of cortisol increased pre-prodynorphin mRNA levels in the arcuate nucleus of ewes, compared with control animals. Lipopolysaccharide injection reduced the expression of Fos protein in kisspeptin cells in the arcuate nucleus observed at the time of the preovulatory LH surge (Fergani et al 2017), indicating reduced activation of the kisspeptin neurons at this time due to the stress of the toxin. The role of stress in the regulation of preoptic kisspeptin neurons in domestic animals does not appear to have been tested.…”
Section: Stressmentioning
confidence: 92%
“…Further unpublished data cited by Ralph et al (2016) showed that stress-like levels of cortisol increased pre-prodynorphin mRNA levels in the arcuate nucleus of ewes, compared with control animals. Lipopolysaccharide injection reduced the expression of Fos protein in kisspeptin cells in the arcuate nucleus observed at the time of the preovulatory LH surge (Fergani et al 2017), indicating reduced activation of the kisspeptin neurons at this time due to the stress of the toxin. The role of stress in the regulation of preoptic kisspeptin neurons in domestic animals does not appear to have been tested.…”
Section: Stressmentioning
confidence: 92%
“…A mouse GS cell line was established as previously reported [24,28]. Briefly, testes were harvested from neonatal DBA/2 J male mice, and after removing the tunica albuginea, testicular tissues were mechanically dissociated and subjected to a collagenase-trypsin dissociation to obtain a single-cell suspension.…”
Section: Methodsmentioning
confidence: 99%
“…To visualize the progress of spermatogenesis in vitro, cytospin slides were used. After the cells were cytospun, they (cytospins) were fixed, permeabilized, and blocked as previously described (Zheng et al, 2017), followed by overnight incubation at 4 C with primary antibodies (Table S1). For negative controls, primary antibodies were replaced with complementary immunoglobulin G. On the next day, the cytospins were washed and incubated with the corresponding host-specific secondary antibodies (Table S1) and counterstained with DAPI.…”
Section: Cytologymentioning
confidence: 99%